Camouflaged as degraded wax: hygroscopic aerosols contribute to leaf desiccation, tree mortality, and forest decline. (30th July 2018) - Burkhardt, Juergen; Zinsmeister, Daniel; Grantz, David A; Vidic, Sonia; Sutton, Mark A; Hunsche, Mauricio; Pariyar, Shyam
Abstract: Some 40 years ago, air pollution caused widespread forest decline in Central Europe and eastern North America. More recently, high levels of tree mortality worldwide are thought to be driven by rising temperatures and increasing atmospheric drought. A neglected factor, possibly contributing to both phenomena, is the foliar accumulation of hygroscopic aerosols. Recent experiments with experimentally added aerosols revealed that foliar aerosol accumulation can (i) create the microscopic impression of 'wax degradation', considered an important proxy of forest decline associated with air pollution, though the mechanism remains unexplained; and (ii) increase epidermal minimum conductance ( g min ), a measure of cuticular permeability and completeness of stomatal closure—both could lead to reduced drought tolerance. Here, those studies with applied aerosol are extended by addressing plant responses to reduction of ambient aerosol. Scots pine, silver fir, and common oak seedlings were grown for 2 years in greenhouses ventilated with ambient air (AA) or air filtered to remove nearly all aerosol particles (FA). Removal of ambient aerosol prevented the development of amorphous structures viewed in the electron microscope that have typically been interpreted as degraded waxes. Lower g min values suggested that FA plants had better stomatal control and therefore greater drought tolerance than AA plants. The co-occurrence of apparent wax degradation and reduced drought tolerance in AA plants suggests a common cause. This may be mediated by the deliquescence and spreading of hygroscopic aerosols across the leaf surface. The liquid film produced may penetrate the stomata and facilitate unproductive stomatal transpiration. In this way, aerosol pollution may enhance the impacts of atmospheric drought, and may damage trees and forests on large spatial scales.